Physical trends in amorphous carbon: a tight-binding molecular-dynamics study - Kopidakis, Georgios; Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2004)
Tight-binding molecular dynamics simulations reveal interesting physical trends in amorphous carbon networks. The variation of sp3 fraction, or mean coordination, is found to be linear over the whole possible range of densities. The density at the floppy transition is ∼0.5 g cm-3, while the density of "amorphous diamond" is ∼3.3 g cm -3. The bulk modulus vanishes at the floppy transition, having a critical coordination near 2.4, and its variation with the mean coordination has a scaling exponent of 1.5, confirming the constraint-counting model of Phillips and Thorpe. A hypothetical fully tetrahedral network has a bulk modulus of 360 GPa, about 15% lower than diamond's. The bulk modulus is also found to vary with the average bond length d̄ as (d̄)35. The homopolar gap of "amorphous diamond" is ∼11.5 eV, compared to ∼14 eV for diamond.
Keywords: Carbon; Density; Elasticity; Molecular dynamics